Facile synthesis of Al2O3-Pt nanocomposite and its catalytic activity. (31st October 2017) - Das, Subhasis; Bordoloi, Ankur; Kumar Ghosalya, Manoj; Gopinath, Chinnakonda S; Bala, Tanushree
Abstract: Pt nanoparticles were synthesized on γ -alumina support in presence of oleic acid which was found to prevent clustering of Pt nanoparticles on the support. Various percentage of Pt loading on the alumina changed the catalytic activity for preferential oxidation of CO at relatively low temperature in H2 rich stream. Pt nanoparticles when synthesized in absence of oleic acid, were all clustered and did not have any catalytic activity. The presence of oleic acid promoted stability preventing agglomeration of Pt nanoparticles. The catalyst thus prepared was characterized thoroughly and their catalytic activity was studied in details.